Joseph Glauber, "Who Will Feed India? The Political Economy of India’s Agricultural Policies and Implications for the Future" - Glauber, Joseph W. (2019)
Joseph Glauber POLICY SEMINAR Who Will Feed India? The Political Economy of India’s Agricultural Policies and Implications for the Future Co-Organized by IFPRI and the Center for the Advanced Study of India (CASI) MAR 22, 2019 - 12:15 PM TO 01:45 PM EDT